EFFORTS TO ENHANCE INDONESIAN ECONOMIC COOPERATION WITH MIDDLE EASTERN COUNTRIES POST THE ARABIC SPRING - Haryadi, Haryadi; Baidawi, Ahmad (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
The Middle East region is a very strategic area for countries in the world because the Middle East Region is an area that has a lot of potential wealth of natural resources in the form of oil, the Middle East is also an area that is a crossroads and the origin of several world civilizations, such as Asian, African, and European cultures. departing from the reasons above, there are many hopes from the Indonesian people to establish cooperation with several countries in the Middle East Region, especially in the economic and political fields. many forms of cooperation can be carried out between Indonesia and Middle Eastern Countries apart from economic and political issues. such as cultural and social issues. The method used in this research is descriptive qualitative research. From the results of the analysis, we can conclude that Cooperation between Indonesia and the countries in the Middle East Region in the economic, political, social, and cultural fields has been carried out in many ways, such as with Saudi Arabia, Iran, and Egypt. However, the cooperation that has existed to this day has not been maximized, especially in the economic field. it is hoped that in the future with the end of the Arab Spring in the Middle East, the cooperation between Indonesia and Middle Eastern countries can be further improved and better.